Collective Civic Action in Multicultural Neighbourhoods: Two Cases in Melbourne. (15th December 2017) - Dekker, Karien; Lee, Julian C.H.; Phipps, Peter
Abstract: The paper provides tentative empirical evidence against Robert D. Putnam's claim that ethnic diversity is a threat to collective civic action, and finds support for Robert J. Sampson's proposition that established organisations foster collective civic action. The aim of this paper is twofold: to describe: (i) the ways in which volunteers and professionals make sense of and understand the multicultural neighbourhood; and (ii) how that impacts on collective civic action in the neighbourhood. The paper takes a small scale mixed‐methods approach (9 semi structured interviews and a small scale quantitative survey (N = 39)), comparing two neighbourhoods with similar characteristics in terms of ethnic diversity and socio‐economic problems. The findings show that problems associated with ethnicity are not the most pressing ones for recent migrants. Instead they struggle with work, housing, a lack of supportive networks, unfamiliarity with the educational system, and language problems. The paper concludes that the multicultural discursive framework is a salutary one for those working and living in ethnically diverse neighbourhoods.